English medium teaching at crisis: towards bilingual education in Hong Kong - Dan Lu (Penerbit UKM, 2002)
A language originally brought in by the British colonial rule in 1841, English used to be the major medium of instruction in Hong Kong educational system. An important debate in today’s Hong Kong's education is on the issue of the continuity of English-medium education. A significant change since 1998 is that the local vernacular Cantonese has replaced English as the medium of instruction in most secondary schools. Integrating theoretical framework into the case of Hong Kong, this paper examines the wisdom and the long-term effects of this policy change. Acknowledging that mother tongue education may facilitate acquisition of knowledge, it appears that the Hong Kong Government’s selection was not well planned and has eroded the principle of bilingual education, which runs counter to its proposed objective of “two written codes and three spoken codes”. The paper points out that mixed code is unavoidable and universal in any bilingual society and therefore, it is irrational to regard it as the culprit of the decline of students’ language competence. In face of the growing role of English in the world, the restricted use of English in education may cause an undesirable impact. The issue of language in education cannot be separated from the objective of language education. In short, the Hong Kong Government’s well-intentioned goal of effective language education for the challenges of the new millennium might, ironically, be a case of linguistic myopia.